2003
DOI: 10.1104/pp.103.020800
|View full text |Cite
|
Sign up to set email alerts
|

AtCHIP, a U-Box-Containing E3 Ubiquitin Ligase, Plays a Critical Role in Temperature Stress Tolerance in Arabidopsis

Abstract: The Arabidopsis gene AtCHIP encodes a protein with three tetratricopeptide repeats and a U-box domain, which is structurally similar to the animal CHIP proteins, a new class of E3 ubiquitin ligases. Like animal CHIP proteins, AtCHIP has E3 ubiquitin ligase activity in vitro. AtCHIP is a single-copy gene, and its transcript is up-regulated by several stress conditions such as low and high temperatures. However, increased AtCHIP expression alone was not correlated with increased stress tolerance; in fact, overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
150
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(161 citation statements)
references
References 33 publications
9
150
0
2
Order By: Relevance
“…7 and 8). The more sensitive phenotype of 35STCaPUB1 lines to drought and salinity is reminiscent of the Arabidopsis U-box AtCHIP-overexpressing plants, which are hypersensitive to extreme temperatures, indicating that increased AtCHIP or CaPUB1 alone might not be enough for enhancing stress tolerance (Yan et al, 2003). Closer inspection revealed that the individual transgenic roots had increased numbers of small-sized cells around the cortex, endodermis, and stele, resulting in disordered, highly populated cell layers relative to control roots (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 and 8). The more sensitive phenotype of 35STCaPUB1 lines to drought and salinity is reminiscent of the Arabidopsis U-box AtCHIP-overexpressing plants, which are hypersensitive to extreme temperatures, indicating that increased AtCHIP or CaPUB1 alone might not be enough for enhancing stress tolerance (Yan et al, 2003). Closer inspection revealed that the individual transgenic roots had increased numbers of small-sized cells around the cortex, endodermis, and stele, resulting in disordered, highly populated cell layers relative to control roots (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that the Arabidopsis U-box AtCHIP transcript was induced significantly by extreme temperatures (Yan et al, 2003). Overexpression of AtCHIP rendered Arabidopsis plants more sensitive to both low and high temperatures Yan et al, 2003). AtCHIP was subsequently reported to interact with an A-subunit of protein phosphatase 2A and suggested to be involved in the ABA-related stress-signaling pathway (Luo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CHIP was also found to be able to promote formation of Lys63-linked polyubiquitin chains in collaboration with Uev1a-Ubc13 in vitro [75]. In plants, the Arabidopsis CHIP gene AtCHIP is upregulated upon temperature stress [76]. However, overexpression of AtCHIP in Arabidopsis rendered plants more sensitive to both low-and high-temperature treatments, suggesting that CHIP's function in plants is complex and it warrants further detailed characterization.…”
Section: U-box-type E3 Ligases Are Newly Identified Members Of the Ubmentioning
confidence: 98%
“…In contrast, the homology of this protein to the TPR motifs of hCHIP is very weak, and it does not contain a mixed charge region. It nevertheless seems to function as a bona fide CHIP protein (9). No CHIP homologues exist in Saccharomyces cerevisiae and Schizosaccharomyces pombe.…”
mentioning
confidence: 99%